International-legal aspects of combating corruption (Journal of actual problems of jurisprudence, 2018)
Authors consider the main scientific and organizational problems related to corruption that prevent process of social-economy development, development of market economy, attracting investment and affect negative to political and public institute of democratic country, represents serious danger to the future of country.Some of the conventions against corruption are analyzed in the article. Appropriate conclusions were made based on the opinions of scholars and experts in this field.The authors, analysing the large theoretical and practical material made conclusions and recommendations for improvement of anti-corruption measures.Key words: anticorruption, anticorruption strategy, the UN Convention, States Parties.